Modern research methods in management - Linkova, Olena (National Technical University "Kharkiv Polytechnic Institute", 2025)
The educational component "Modern Research Methods in Management" covers all aspects of conducting scientific research in management. During the training, applicants apply modern tools and technologies for searching, processing and analyzing information, use the principles and methods of management sciences, and the methodology of scientific research when conducting their own research in the field of management. The means of achieving this will be the analysis of management methods when solving the chosen scientific topic by the applicant.
Keywords: syllabus; research on management systems; organization as a society; the evolution of management; formal-logical research methods